(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
E-HogMo is an E-commerce web based application that will facilitate the buying and selling process of the sellers (small scale farmers) and buyers (meat vendors, hog raisers and meat processors). The app aims to improve the process of taking longer time to search for qualified sellers and prevent high cost of product due to the big commissions taken by the middlemen or agents. And given the threat of the African Swine Fever (ASF) this app is required to market livestock that are ASF free. This study focuses on determining the user experience design of a livestock E-commerce application using the Design Thinking (DT) methodology. The Empathy, Define, Ideate, Prototype, and Test phases of the Design Thinking approach were used to identify the present scenario or experiences, problems and issues, and potential solutions to their concerns. A Focus Group Discussion (FGD) was conducted to fifteen (15) participants consisting of hog raisers and buyers to determine the features and functionalities that the users required based on their needs. A prototype design which includes Registration, Search by products, Managing products, Virtual Farm Tour, Ordering, Payment and Dashboards modules was created and presented to the users for validation. The results show the significance of the features in addressing the current problems in the buying and selling process such as it will lessen the time to search for quality products, it will help to regulate the costs of the livestock and meat products and prevent selling of swine that are infected with ASF.